Green agenda with UiTM Green Centre (UGC) - UiTM, UGC (UiTM Green Centre, 2025)
UiTM Green Centre (UGC) visitation to UiTM Perak has taken place to see the green agenda that has been made by UiTM Perak. This visit was led by UGC Director, Prof Madya Ts Dr Khairi Khalid.